2019
DOI: 10.3389/fpsyg.2019.00660
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Mechanisms of Metacognitive Therapy – An Experimental Paradigm

Abstract: Introduction The neurobiological mechanisms underlying the clinical effects of psychotherapy are scarcely understood. In particular, the modifying effects of psychotherapy on neuronal activity are largely unknown. We here present data from an innovative experimental paradigm using the example of a patient with treatment resistant obsessive-compulsive disorder (trOCD) who underwent implantation of bilateral electrodes for deep brain stimulation (DBS). The aim of the paradigm was to examine the shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Deep brain stimulation (DBS) has emerged as a promising treatment option for patients with trOCD (9)(10)(11)(12). Common targets of DBS were summarized in recent reviews and include white matter trajectories (anterior limb of the internal capsule [ALIC], inferior thalamic peduncle, median forebrain bundle), and gray matter subcortical nuclei (nucleus accumbens, nucleus subthalamicus, bed nucleus of the stria terminalis [BNST]) (13)(14)(15). A guideline by the American Society for Stereotactic and Functional Neurosurgery and the Congress of Neurological Surgeons (16) came to the conclusion that there is level I evidence for bilateral subthalamic nucleus and level II evidence for bilateral nucleus accumbens DBS in trOCD (16).…”
Section: Introductionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) has emerged as a promising treatment option for patients with trOCD (9)(10)(11)(12). Common targets of DBS were summarized in recent reviews and include white matter trajectories (anterior limb of the internal capsule [ALIC], inferior thalamic peduncle, median forebrain bundle), and gray matter subcortical nuclei (nucleus accumbens, nucleus subthalamicus, bed nucleus of the stria terminalis [BNST]) (13)(14)(15). A guideline by the American Society for Stereotactic and Functional Neurosurgery and the Congress of Neurological Surgeons (16) came to the conclusion that there is level I evidence for bilateral subthalamic nucleus and level II evidence for bilateral nucleus accumbens DBS in trOCD (16).…”
Section: Introductionmentioning
confidence: 99%
“…Winter et al wondered about the neuronal base of the MCT and investigated the short-term effect of the MCT on neuronal local field potentials at baseline and after 5 sessions of the MCT treatment period by using bilateral electrodes in the patient who suffered from the implantation of deep brain stimulation. 36 They found that the symptoms of OCD reduced after 5 sessions of the MCT treatment, accompanying a reduction in the relative power of theta-band activity and an increase in alpha, beta, and gamma-band activity. Rupp et al 37 in another study examined the efficacy of the DM and cognitive restructuring as stand-alone interventions in patients with OCD.…”
Section: Resultsmentioning
confidence: 97%
“…However, due to the high stakes of undergoing psychiatric neurosurgery, fostering trustful and enduring relationships is essential as well as followup offers that engage with personal patient needs and account for caregiver perspectives in setting psychiatric follow-up care provisions [77]. For psychiatric neurosurgical research, paying attention to the humanistic dimensions in medicine also requires to evaluate these treatments using patient-reported outcomes such as quality of life that encompass broader indicators of disease burden and patient-relevant outcomes [144].…”
Section: Discussion: Recommendation For Transferring Research To the ...mentioning
confidence: 99%